1977
DOI: 10.1161/01.cir.56.6.924
|View full text |Cite
|
Sign up to set email alerts
|

Occult constrictive pericardial disease. Diagnosis by rapid volume expansion and correction by pericardiectomy.

Abstract: of dobutamine on regional myocardial blood flow and ventricular performance during acute and chronic myocardial ischemia in dogs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0
2

Year Published

1981
1981
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(45 citation statements)
references
References 13 publications
(3 reference statements)
0
43
0
2
Order By: Relevance
“…Threeyear survival in the patients with ILD was 82.5% (95% CI 78.0-87.0). Survival at 5 years was similar in patients with a mean PAP of Յ20 mm Hg and those with a mean PAP of [21][22][23][24] (Figure 4). Survival at 3 years was 90% (95% CI 72-100) in the group of patients with rapid progression.…”
Section: Resultsmentioning
confidence: 83%
“…Threeyear survival in the patients with ILD was 82.5% (95% CI 78.0-87.0). Survival at 5 years was similar in patients with a mean PAP of Յ20 mm Hg and those with a mean PAP of [21][22][23][24] (Figure 4). Survival at 3 years was 90% (95% CI 72-100) in the group of patients with rapid progression.…”
Section: Resultsmentioning
confidence: 83%
“…This challenge is based on studies that show marked increases in PWP (Ͼ 7 mm Hg) in patients with LV dysfunction with preserved systolic function rapidly given up to 1,000 mL of saline solution. 17 We found that little additional increase in PWP was obtained with a fluid challenge of Ͼ 500 mL; therefore, 500 mL was used in our protocol. Two patients with PVH underwent RHC at outside institutions, neither of whom received inhaled nitric oxide or a fluid challenge.…”
Section: Study Patientsmentioning
confidence: 99%
“…For clinical suspicion of SSc-related occult constrictive pericarditis (dyspnea on exertion out of proportion to pulmonary function test values), right and left cardiac catheterization with a fluid challenge (1000 cc bolus of normal saline over 10 minutes) may be required for diagnosis 19 .…”
Section: Rheumatologymentioning
confidence: 99%